Hearing Loss in Diabetic Patients Linked with Glycolyzed Hemoglobin A1C - Muhammad Afzal, Zaid Aslam, Ali Umair (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Glycolyzed haemoglobin A1c (HbA1c) and hearing loss in diabetic individuals are the primary goals of the present research. Study Design: Randomized Case Control Place and Duration: THQ Hospital Kamalia. Aug 2021 to Feb 2022. Methods: There were 80 patients of both genders with ages 16-75 years were presented. Detailed demographics of enrolled cases included age, sex, body mass index and comorbidities were recorded after taking informed written consent. Patients were divided in two groups. Group I had 40 diabetic patients and group II had 40 non-diabetic patients. Hearing loss among both groups was compared by different glycolized hemoglobin levels. SPSS 25.0 was used to analyze complete data. Results: There were 32 (80%) males and 8 (20%) female in group I and in group II 24 (60%) males and 16 (40%) females. Mean age in group I was 41.31±5.81 years and had men BMI 24.13±7.15 kg/m2 while in group II mean age was 39.11±4.28 years with mean BMI 22.17±11.32 kg/m2. In group I 18 (45%) patients were smokers and in group II 15 (27.5%) were smokers. Frequency of hearing loss in group I was higher found in 23 (57.5%) patients as compared to non-diabetic patients in only 2 (5%). Frequency of tinnitus, vertigo and dizziness were also significantly higher in diabetic patients with p value <0.05. Conclusion: Patients with diabetes mellitus may suffer from impaired hearing and balance even if they do not show any symptoms. As a result, early rehabilitative care should be established to prevent future difficulties.